Toxic Effect of Deltamethrin on Some Hematological and Biochemical Parameter of Male Rats - Abdulrahman Aljali; Hamzah Othman; Safia Hazawy (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Deltamethrin (Dm) is a synthetic pyrethroid insecticide used worldwide in agriculture, home pest control, protection of foodstuff and disease vector control. The aim of this study was to investigate the propensity of deltamethrin to induce oxidative stress and changes in hematology, biochemical parameters and teratogenic effect in male rats. Methods. Fifteen adult male albino Wistar rats were divided into three groups Group 1 served as control and received distilled water orally. Group 2 received DM 1/10 LD 50 (0.6 mg/kg BW) orally for 30 days, and Group 3 received DM 1/20 LD 50 (0.3 mg/kg BW) orally for 30 days. Results. Deltamethrin caused significant changes of some hematological parameters (red blood cells (RBC), hemoglobin (Hb), hematocrit (PCV), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and white blood cells (WBC)) in treated rats compared to controls. Significant increases in the levels of hepatic markers enzymes (alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP). Furthermore, renal markers such as urea and creatinine were increased in deltamethrin treated rats. Conclusion. deltamethrin is harmful on animal and human health.